Analysis of Students' Difficulties in Determining Main Idea in Reading Text in Grade V - Yunita, Rahma; Safrizal, Safrizal; Komalasari, Elis (Al-Hijr: Journal of Adulearn World, 2023)
This research is motivated by students' problems when learning to determine the main idea. The aim of this research is to find out the problems experienced by students in learning to determine the main idea in a text. The type of research used in this research is a case study. This research uses a qualitative approach with the type of case study research chosen using a purposive sampling technique. This research was conducted on class V teachers and class V students at SD N 20 Paninjauan. The instrument of this research is the researcher himself. Data collection in this research is interviews and documentation, the data and information that has been obtained is then analyzed using the Milles and Huberman model. The results of the research, this research shows that the implementation of class V Indonesian language content learning with the material of determining the main idea only uses the lecture method and in implementing the learning the media is not used enough to support the learning process, and the students' ability to read quickly is very low. And when reading texts that are too long, students do not understand the vocabulary in the text.